What does it take to give your trust online? an analysis on building trust on online commerce in the Philippines - Esguerra, Chabely V.
E-commerce in the Philippines is projected to grow to almost trillion pesos in sales by 2025. And yet, we are still behind our South East Asian counterparts like Thailand and Indonesia. The potential of e-commerce in the Philippines is promising with the fast growth of internet penetration and infrastructure upgrade including fulfillment services, faster internet service, etc., but it is hindered by the market itself; Filipinos do not trust online commerce. The main problem that this research paper tried to find answers to is about this online trust. What would it take for Filipinos to trust online commerce?